A drug utilization study of antiepileptic drugs uses in a tertiary care teaching hospital of India - Mandal, Soumitra; Donepudi, Aruna; Afshan, Jabeen Shaik; Turaga, Suryaprabha (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Epilepsy is a disorder characterized by repeated seizures due to the disorder of the neurons. Epilepsy needs life-long medical therapy. It is managed by polytherapy. Drug utilization studies help to determine rational combinations of drug use in epilepsy. Aims and objectives of the study were to analyses the drug utilization pattern of anti-epileptics and common types of epileptic seizures and to determine the safety of antiepileptic drugs (AEDs). Methods: It was a prospective, cross-sectional, observational study. Patients attending neurology epilepsy OPD with h/o seizures and taking at least one antiepileptic were recruited. Data was collected by taking demographic details including brief history of disease, clinical examination and reviewing OPD prescription. Details were recorded in case record form. Results: We recruited 102 participants (57 male and 45 females) of mean age 29.68±10.52. Mean age of onset of epilepsy was 18.9±10.5 years. Among them 77 (75.4%) were diagnosed as generalized tonic clonic seizures and 18 (17.6%) were diagnosed as focal seizures. Monotherapy was given in 31 (30.3%) patients while polytherapy was given in 71 (69.7%) patients. Valproic acid was most commonly used monotherapy (12 patients). No fixed drug combinations were used. Clobazam in 55 (53.9%) patients and valproic acid in 53 (51.9%) patients were prescribed. The other AEDs prescribed were lamotrigine, oxcarbazepine, carbamazepine, lacosamide, zincosamide, perampanel, and phenytoin. All antiepileptics were prescribed in brand name. The prescribed daily dose (PDD) was less than defined daily dose (DDD) as per anatomical therapeutic chemical (ATC) classification. Two adverse effects were reported during study period. They were mood change and blurring of vision in two different patients. Conclusions: The PDD was less than DDD as per ATC classification. Awareness should be created among neurologists to prescribe more generic drugs because of their cost effectiveness. Studies are needed with larger sample size to analyze the drug utilization patterns which helps in the planning of reduction of expenditure for the patient without compromising efficacy.